2016
DOI: 10.1080/14728214.2016.1241232
|View full text |Cite
|
Sign up to set email alerts
|

Emerging drugs to reduce abnormal β-amyloid protein in Alzheimer’s disease patients

Abstract: Currently available drugs against Alzheimer's disease (AD) target cholinergic and glutamatergic neurotransmissions without affecting the underlying disease process. Putative disease-modifying drugs are in development and target β-amyloid (Aβ) peptide and tau protein, the principal neurophatological hallmarks of the disease. Areas covered: Phase III clinical studies of emerging anti-Aβ drugs for the treatment of AD were searched in US and EU clinical trial registries and in the medical literature until May 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 122 publications
4
74
0
2
Order By: Relevance
“…Currently, the FDA approved few AD drugs, such as acetylcholinesterase inhibitors, N-Methyl-D-aspartate (NMDA) receptor antagonists, monoclonal antibodies for anti-Aβ, inhibitor for BACE, inhibitor for RAGE receptor and the combination drug of cromolyn sodium and ibuprofen [12]. In the past few decades, various natural compounds (phytochemicals and herbs), naturally occurring polyphenol (resveratrol, trans-3, 4', 5-trihydroxystilbene), and nutritional supplements (i.e., cinnamon extract and savory) with anti-oxidant and anti-inflammatory activities have shown potential as a beneficial counteractive approach to prevent Aβ neurotoxicity by inhibiting oligomeric formation, alternative counter measure of Tau malfunction as well as correcting memory impairment [1316].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the FDA approved few AD drugs, such as acetylcholinesterase inhibitors, N-Methyl-D-aspartate (NMDA) receptor antagonists, monoclonal antibodies for anti-Aβ, inhibitor for BACE, inhibitor for RAGE receptor and the combination drug of cromolyn sodium and ibuprofen [12]. In the past few decades, various natural compounds (phytochemicals and herbs), naturally occurring polyphenol (resveratrol, trans-3, 4', 5-trihydroxystilbene), and nutritional supplements (i.e., cinnamon extract and savory) with anti-oxidant and anti-inflammatory activities have shown potential as a beneficial counteractive approach to prevent Aβ neurotoxicity by inhibiting oligomeric formation, alternative counter measure of Tau malfunction as well as correcting memory impairment [1316].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we explored the potential anti-Alzheimer’s effect of a CG extract, in which Maysin and its derivatives could exert protective effects for neurons by inhibiting oligomeric Aβ42 aggregation and β-Secretase (BACE) and decreasing neuronal toxicity by using neuronal PC12 cells as an in vitro model [20]. BACE, a potential drug candidate was examined its functional advantage for early phase preclinical familial AD patients along with inhibitor of RAGE (advanced glycation end products) in a Phase III clinical development stage [12]. In this study, our findings indicate that the natural Maysin and its derivative flavonoid compounds in EA-CG extract significantly prevented AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cognitive decline of AD subjects is not related directly to plaque burden (Tu et al, 2014), much of the current focus on therapeutics for AD has been on the development of monoclonal antibodies against Aβ or its aggregates, including the drugs aducanumab, gantenerumab, and solanezumab which are currently in phase III clinical trials (Panza et al, 2016; Cavanaugh et al, 2014). Interim results from double blind studies have suggested aducanumab reduces plaques and Aβ in human and AD mouse brain and slows somewhat the cognitive decline in humans (Sevigny et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Current immunotherapeutic approaches to target Aβ have used passive humanised antibodies to enhance removal of Aβ from the brain with the aim of slowing or halting the progression of AD [49]. To date these have had little success [49][50][51][52].…”
Section: Antibody Reactivities and Their Relevance To App Proteolyticmentioning
confidence: 99%
“…To date these have had little success [49][50][51][52]. Bapineuzumab, Table 1, is based on the monoclonal antibody 3D6 directed towards an N-terminal epitope and Solanezumab, directed at an epitope from the Aβ (13-28) central region [53].…”
Section: Antibody Reactivities and Their Relevance To App Proteolyticmentioning
confidence: 99%